2021
DOI: 10.3390/agriculture11020143
|View full text |Cite
|
Sign up to set email alerts
|

Foodshed, Agricultural Diversification and Self-Sufficiency Assessment: Beyond the Isotropic Circle Foodshed—A Case Study from Avignon (France)

Abstract: The regionalization of food systems in order to shorten supply chains and develop local agriculture to feed city regions presents particular challenges for food planning and policy. The existing foodshed approaches enable one to assess the theoretical capacity of the food self-sufficiency of a specific region, but they struggle to consider the diversity of existing crops in a way that could be usable to inform decisions and support urban food strategies. Most studies are based on the definition of the area req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…The foodshed approach has also been used to estimate the size of the foodshed required to meet a given rate of food self-sufficiency, taking into account different food system scenarios in terms of food groups, food production systems (conventional versus organic), diets, and levels of food loss and waste (e.g., the Metropolitan Foodshed and Self-sufficiency Scenario: MFSS; [17]). Thus, in addition to food production capacity based on biophysical conditions, our recent work considered socioeconomic features driving the flows and distribution networks of locally-grown food [7]. Our findings showed that analysis needs to be shifted from size assessment of the foodshed represented as an isotropic circle around the city to commodity-group-specific spatial configuration of the foodshed [7].…”
Section: Foodshed Approachesmentioning
confidence: 94%
See 1 more Smart Citation
“…The foodshed approach has also been used to estimate the size of the foodshed required to meet a given rate of food self-sufficiency, taking into account different food system scenarios in terms of food groups, food production systems (conventional versus organic), diets, and levels of food loss and waste (e.g., the Metropolitan Foodshed and Self-sufficiency Scenario: MFSS; [17]). Thus, in addition to food production capacity based on biophysical conditions, our recent work considered socioeconomic features driving the flows and distribution networks of locally-grown food [7]. Our findings showed that analysis needs to be shifted from size assessment of the foodshed represented as an isotropic circle around the city to commodity-group-specific spatial configuration of the foodshed [7].…”
Section: Foodshed Approachesmentioning
confidence: 94%
“…Current research is highlighting foodshed approaches as a way of identifying the farmland areas functionally linked to cities that could be involved in new short food supply chains [7]. In this paper, we first briefly sketch the state-of-the-art concerning the notion of foodshed.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in addition to food production capacity based on biophysical conditions, our recent work considered socioeconomic features driving the flows and distribution networks of locallygrown food. Our findings showed that analysis needs to be shifted from size assessment of the foodshed represented as an isotropic circle around the city, to commodity-group-specific spatial configuration of the foodshed [7]. The aim of the present study is to explore foodshed assessment as a complex of complementary entities, i.e., the "foodshed archipelago".…”
Section: Foodshed Approachesmentioning
confidence: 98%
“…Following previous work [7], we defined a radius of 100 km around Avignon, a medium-sized city located in south-eastern France. The selected area incorporates three different administrative regions and ten different provinces (the French départements): Bouches-du-Rhône, Vaucluse, Var, Hautes Alpes in the Provence-Alpes-Côte d'Azur region, Gard, Hérault, Lozère in the Occitanie region and Ardèche and Drome in the Auvergne-Rhone-Alpes region (Figure 1).…”
Section: Study Areamentioning
confidence: 99%
“…According to Schreiber et al (2021), they can be classified in three types: (a) agricultural production capacity, (b) food flow and (c) hybrid analyses. The majority of the assessments are based on assessing the potential agricultural production capacity in order to feed the specific population of the city-region (i.e., foodshed) (Joseph et al, 2019;Zasada et al, 2019;Kurtz et al, 2020;Vicente-Vicente et al, 2021b); or to assess more specific issues as part of sustainability impact and ecosystem services assessments of regional food systems and land uses (Swiader et al, 2018;Tavakoli-Hashjini et al, 2020). The food flow assessments map consumers and producers, being thus useful when studying distribution networks (Karg et al, 2016;Wegerif and Wiskerke, 2017;Moschitz and Frick, 2020).…”
Section: Decision Support Systems For Assessing Food Systems Sustaina...mentioning
confidence: 99%